Voices of bereavement : a casebook for grief counselors - Beder, Joan, 1944- (Series in death, dying, and bereavement., 2004)
This book is built on the premise that individuals and family members can be helped through their bereavement experience and that there are specific skills and interventions that guide a counselor in this work.